Design, synthesis and pharmacological evaluation of 4-(3-chloro-4-(3-cyclopropylthioureido)-2-fluorophenoxy)-7-methoxyquinoline-6-carboxamide (WXFL-152): a novel triple angiokinase inhibitor for cancer therapy - Yuqin Yao; Zhuowei Liu; Manyu Zhao; Zhengxia Chen; Peng Li; Yang Zhang; Yuxi Wang; Chengjian Zhao; Chaofeng Long; Xiaoxin Chen; Jinliang Yang (Elsevier, 2020)
Angiokinases, such as vascular endothelial-, fibroblast- and platelet-derived growth factor receptors (VEGFRs, FGFRs and PDGFRs) play crucial roles in tumor angiogenesis. Anti-angiogenesis therapy using multi-angiokinase inhibitor has achieved great success in recent years. In this study, we presented the design, synthesis, target identification, molecular mechanism, pharmacodynamics (PD) and pharmacokinetics (PK) research of a novel triple-angiokinase inhibitor WXFL-152. WXFL-152, identified from a series of 4-oxyquinoline derivatives based on a structure-activity relationship study, inhibited the proliferation of vascular endothelial cells (ECs) and pericytes by blocking the angiokinase signals VEGF/VEGFR2, FGF/FGFRs and PDGF/PDGFRβ simultaneously in vitro. Significant anticancer effects of WXFL-152 were confirmed in multiple preclinical tumor xenograft models, including a patient-derived tumor xenograft (PDX) model. Pharmacokinetic studies of WXFL-152 demonstrated high favourable bioavailability with single-dose and continuous multi-dose by oral administration in rats and beagles. In conclusion, WXFL-152, which is currently in phase Ib clinical trials, is a novel and effective triple-angiokinase inhibitor with clear PD and PK in tumor therapy.